The Bacterial Wilt Reservoir Host Solanum dulcamara Shows Resistance to Ralstonia solanacearum Infection - Sebastià, Pau; de Pedro-Jové, Roger; Daubech, Benoit; Kashyap, Anurag; Coll, Núria S.; Valls, Marc (Frontiers in Plant Science, 2021)
Ralstonia solanacearum causes bacterial wilt, a devastating plant disease, responsible for serious losses on many crop plants. R. solanacearum phylotype II-B1 strains have caused important outbreaks in temperate regions, where the pathogen has been identified inside asymptomatic bittersweet (Solanum dulcamara) plants near rivers and in potato fields. S. dulcamara is a perennial species described as a reservoir host where R. solanacearum can overwinter, but their interaction remains uncharacterised. In this study, we have systematically analysed R. solanacearum infection in S. dulcamara, dissecting the behaviour of this plant compared with susceptible hosts such as tomato cv. Marmande, for which the interaction is well described. Compared with susceptible tomatoes, S. dulcamara plants (i) show delayed symptomatology and bacterial progression, (ii) restrict bacterial movement inside and between xylem vessels, (iii) limit bacterial root colonisation, and (iv) show constitutively higher lignification in the stem. Taken together, these results demonstrate that S. dulcamara behaves as partially resistant to bacterial wilt, a property that is enhanced at lower temperatures. This study proves that tolerance (i.e., the capacity to reduce the negative effects of infection) is not required for a wild plant to act as a reservoir host. We propose that inherent resistance (impediment to colonisation) and a perennial habit enable bittersweet plants to behave as reservoirs for R. solanacearum.